An exploration into the value of protective factors in violence risk assessment of psychiatric inpatients - Judges, Rachel C. (2016)
This thesis explores the value of including protective factors in the violence risk assessment and risk management processes of forensic mental health services. More specifically it investigates whether assessment of protective factors improves predictive accuracy of violence risk assessment tools, and discusses the implications for clinical practice. The impact on patient motivation to change is also considered. A critique is presented of the Historical Clinical Risk-20 Version 3 (HCR-20V3; Douglas, Hart, Webster, & Belfrage, 2013), one of the most popular and widely used violence risk assessment tools. Despite its popularity and good measurable properties, the HCR-20V3 does not include an assessment of protective factors. A systematic review examined research investigating the predictive accuracy of the three violence risk assessment tools recommended for use in forensic mental health services in the National Health Service: HCR-20V3, the Structured Assessment of Protective Factors (SAPROF; de Vogel, de Ruiter, Bourman, & de Vries Robbé, 2012), and the Short Term Assessment of Risk and Treatability (START; Webster, Martin, Brink, Nicolls, & Desmarais, 2004). The SAPROF had superior predictive accuracy of absence of violence compared to the other measures; however, limited reliability and validity evidence was found for its use in English forensic inpatient settings. An empirical research project conducted a prospective validation study of the SAPROF, also reporting on the reliability and validity of the measure across a number of domains, and in relation to the HCR-20V3 and START. The SAPROF demonstrated better absence of violence risk predictive abilities than the HCR-20V3 and the START (presence of violence risk); combined use of the SAPROF and HCR-20V3 significantly increased predictive accuracy of presence of violence risk. Finally, a single case study explores the impact of collaborative risk assessment and management training on a patient’s motivation to engage in treatment and interventions to manage risk. Collaborative risk assessment had a positive impact on motivation; however it was not reliably or clinically significant. This thesis provides positive research evidence for the inclusion of protective factors in the violence risk assessment and management process.